Development of Electrodes for Cryopreservation of Stem Cells by Electroporation-Assisted Loading with Sucrose - Schwäblein, Anna; Khayyat, Diaa; Leal Marin, Sara; Glasmacher, Birgit (Problems of Cryobiology and Cryomedicine, 2023)
Probl Cryobiol Cryomed 2023; 33(4):295